2020
DOI: 10.1007/s00134-020-06281-2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and quantitative CT-scan characterization of COVID-19 and typical ARDS: a matched cohort study

Abstract: Purpose: To investigate whether COVID-19-ARDS differs from all-cause ARDS. Methods: Thirty-two consecutive, mechanically ventilated COVID-19-ARDS patients were compared to two historical ARDS sub-populations 1:1 matched for PaO 2 /FiO 2 or for compliance of the respiratory system. Gas exchange, hemodynamics and respiratory mechanics were recorded at 5 and 15 cmH 2 O PEEP. CT scan variables were measured at 5 cmH 2 O PEEP. Results: Anthropometric characteristics were similar in COVID-19-ARDS, PaO 2 /FiO 2-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
208
4
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(248 citation statements)
references
References 32 publications
26
208
4
10
Order By: Relevance
“…In addition, they found that patients who presented with lower C RS and higher D-dimer values had the greatest mortality risk. In line with these gures, in a small-case series Chiumello and collaborators found that COVID-19 patients presented higher C RS levels in comparison with patients with ARDS from other etiologies and matched levels of hypoxemia [12]. Regrettably, those previous reports did not provide any information on how C RS progressed beyond a punctual assessment during the period of MV.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition, they found that patients who presented with lower C RS and higher D-dimer values had the greatest mortality risk. In line with these gures, in a small-case series Chiumello and collaborators found that COVID-19 patients presented higher C RS levels in comparison with patients with ARDS from other etiologies and matched levels of hypoxemia [12]. Regrettably, those previous reports did not provide any information on how C RS progressed beyond a punctual assessment during the period of MV.…”
Section: Introductionmentioning
confidence: 77%
“…Female sex presented lower C RS than in males (95% CI: -13.8 to -8.5 P < 0.001) and higher body mass index (34.7 ± 10.9 vs 29.1 ± 6.0, p < 0.001). Median (IQR) PEEP was 12 cmH 2 O (10)(11)(12)(13)(14)(15), throughout the range of C RS , while median (IQR) driving pressure was 12.3 (10)(11)(12)(13)(14)(15) cmH 2 O and signi cantly decreased as C RS improved (p < 0.001). No differences were found in comorbidities and clinical management between C RS strata.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the editorial by Goligher, Ranieri and Slutsky [1] as it provides an excellent summary of the results of our study on the characteristics of coronavirus disease 2019 (COVID-19) related acute respiratory distress syndrome (ARDS) [2]. The editorialists recognize that our population of patients with severe COVID-19 exhibited anatomical and physiological characteristics that are distinct from the two matched cohorts of typical ARDS.…”
mentioning
confidence: 98%
“…In a recent article, Chiumello et al approach these questions by comparing the respiratory pathophysiological features of patients with early COVID-19 ARDS to historical controls with classical (non-COVID-19) ARDS [1]. A hallmark of classical ARDS is that hypoxemia results predominantly from atelectasis and consolidation, with a consequent increase in physiological shunt fraction [2,3].…”
mentioning
confidence: 99%